The Impact of Digital Leadership on Sustainable Supply Chain Performance in UK Manufacturing Firms: The Mediating Role of Supply Chain Digital Orientation - Odeh, Odeson Osaiyekemwen; Cavdar, Seyman Caliskan; Bekun, Festus Victor (International Review of Management and Marketing, 2026)
Although digital transformation is critical to sustainability, manufacturing firms face significant challenges in converting digital leadership to sustainable supply chain performance, with the mediation of supply chain digital orientation still insufficiently studied, especially in the UK. A quantitative cross-sectional exploratory study involving 300 senior managers and supply chain professionals of the manufacturing companies in the United Kingdom was carried out through the use of structured questionnaire. With the four null hypotheses, Structural Equation Modelling (SEM) using AMOS was used to test them. All the null hypotheses were rejected as digital leadership had a significant direct effect on sustainable supply chain performance (β = 0.41 and p < 0.001) and a strong influence on supply chain digital orientation (β = 0.67 and p < 0.001). Digital orientation of the supply chain was also a significant influence on the sustainable supply chain performance (β = 0.53, p < 0.001), and partially mediated the relationship between leadership and performance (indirect β = 0.36, p < 0.001). The model accounted for 56% of the variance in sustainable performance. The theoretical extension of the study is theoretical and it is based on Dynamic Capabilities Theory. In practice, firms need to invest in developing their digital leadership. Policy implications include supporting leadership programmes and digital technology incentives. Recommendations include longitudinal designs and cross-national comparative studies. The study finds that digitally competent leaders create digital orientation throughout supply chains which directly contributes to better economic, environmental and social outcomes.